Pengaruh Internal Locus Of Control dan Dukungan Sosial terhadap Prokrastinasi Akademik Mahasiswa FKIP UNS - Aditya Prayoga; Harini Harini; Salman Alfarisy Totalia (Journal on Education, 2023)
This research aims to determine the effect of internal locus of control on student academic procrastination, the effect of social support on student academic procrastination, and the effect of internal locus of control and social support simultaneously on academic procrastination of FKIP UNS students. The research method used is a quantitative descriptive method and data collection techniques using a questionnaire. The sampling technique used probability sampling technique, namely proportionate stratified random sampling with a sample of 378 FKIP UNS students. Validity test using product moment and reliability test using Cronbach's alpha. Data analysis techniques in this study used descriptive statistical analysis, multiple linear regression analysis, t test, and F test. The results of this research indicate that (1) there is a negative and significant effect of internal locus of control on academic procrastination of FKIP UNS students, (2) there is a negative and significant effect of social support on academic procrastination of FKIP UNS students, (3) there is a significant effect simultaneous internal locus of control and social support on academic procrastination of FKIP UNS students.